1997
DOI: 10.1002/(sici)1097-0142(19970215)79:4<796::aid-cncr17>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic discrepancies and their clinical impact in a neuropathology referral practice

Abstract: BACKGROUND During the course of their neuropathology practice, the authors received cases to review in consultation. In some cases, the patients came to the authors' hospital for therapy; in others, the primary pathologists requested a consultation. Because changes in diagnosis might significantly alter patient management, protocol entry, care costs, or the potential for physician liability, the authors determined the frequency and degrees of their disagreements with the original diagnoses submitted to them. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(76 citation statements)
references
References 17 publications
4
69
0
3
Order By: Relevance
“…7 Major disagreement rates show wide variability, ranging from 0.3% to 10%, depending on many factors such as the tissue type, the type of referral (physician requested or routine transfer), and the institution. [8][9][10][11][12][13][14][15][16][17] We are not aware of any studies that have explored the interactions between these 2 types of bias in FNAB DTA studies. In addition and importantly, verification bias and classification bias may interact in unpredictable ways so that it is difficult to estimate the total bias based on the estimated bias due to each component.…”
Section: Introductionmentioning
confidence: 99%
“…7 Major disagreement rates show wide variability, ranging from 0.3% to 10%, depending on many factors such as the tissue type, the type of referral (physician requested or routine transfer), and the institution. [8][9][10][11][12][13][14][15][16][17] We are not aware of any studies that have explored the interactions between these 2 types of bias in FNAB DTA studies. In addition and importantly, verification bias and classification bias may interact in unpredictable ways so that it is difficult to estimate the total bias based on the estimated bias due to each component.…”
Section: Introductionmentioning
confidence: 99%
“…nterinstitutional review of pathology material, either directed by the pathologist or by the patients or clinicians, has been previously studied [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and is often recommended or required by pathology organizations and medical institutions when patients change facilities for treatment. 7,[16][17] These studies have shown that the rate of disagreement depends not only on the type of tissue but also on the type of sampling.…”
mentioning
confidence: 99%
“…Esse método foi escolhido por lidar elegante e eficientemente com a tarefa de encontrar modelos representados por árvores de decisão com complexidade limitada (3) . Ademais, o CART e outros métodos de inteligência artificial têm sido usados com sucesso na geração de modelos diagnósticos em medicina, notadamente através do uso de sistemas especialistas dedutivos e na indução de modelos de conhecimento a partir de uma coleção retrospectiva de casos (6,11,17) .…”
Section: Análise Histopatológica: Reconhecendo E Elaborando Estratégiunclassified
“…A despeito da aparente simplicidade na aplicação dos critérios histológicos de graduação e das notórias particularidades epidemiológicas e radiológicas observadas entre as diferentes gradações dos astrocitomas, a rotina diagnóstica histopatológica permanece laboriosa, sendo marcada pela baixa reprodutibilidade interobservador (3,7,12,19,20,22,24,25) . Mesmo assim, a análise histológica convencional permanece o melhor método diagnóstico e razoável indicador prognóstico para os tumores astrocíticos (3,11,19) .…”
Section: Introductionunclassified
See 1 more Smart Citation